Exploring the complementarities of in situ and ex situ conservation strategies for asian sweetpotato genetic resources: Proceeding of the 3rd International Workshop of the Asian Network for Sweetpotato Genetic Resources (ANSWER), Denpasar, Bali, Indonesia, 2 - 4 October 2001 - Ramanatha Rao, V.; Campilan, D. (2002)
These proceedings have been compiled and jointly edited by CIP and IPGRI-APO based on the papers presented at this workshop dealing with objectives as set by ANSWER (Asian Network for Sweetpotato Genetic Resources) members. They contain the information on the progress made during the three years since the members met last time, but more importantly they record the commitments made by different partners for furthering sweetpotato genetic resources work in Asia. They also contain critical analysis of feasibility of on-farm conservation of sweetpotato diversity. They also contain the recommendations on strategies and approaches proposed at the workshop which will form the basis for future work of ANSWER. I hope that the publication and distribution of this volume will stimulate further research on sweetpotato genetic resources conservation and use in Asia.